Comparative Study of Modified Quantitative Buffy Coat and Two Rapid Tests in Comparison with Peripheral Blood Smear in Malaria Diagnosis in Mumbai, India - Manali M. Kocharekar; Sougat S. Sarkar; Debjani Dasgupta (Journal of Parasitology Research)
In order to identify a quick and reliable technique for accurate diagnosis of malaria, study of the efficiency of the tests such as Parahit total (HRPII & aldolase Ag), Advantage mal card (parasite specific LDH), and modified QBC was done in comparison with conventional blood smear microscopy. One hundred patients infected with P. vivax and 101 infected with P. falciparum were included in this study. The sensitivity of Parahit total, Advantage mal card, and modified QBC for P. falciparum detection was 70.3, 95%, and 98%, and specificity was 98%, 98%, and 96%, respectively. The sensitivity of Parahit total, Advantage mal card, and modified QBC for P. vivax detection was 73%, 97.0%, and 98%, respectively, and specificity of all the tests was 98%. On day 15, in falciparum arm, Advantage mal card and Parahit total showed 8 (7.92%) and 59 (58.41%) false positives. On day 15, in vivax arm, Parahit total revealed 52% false positives. The study indicated that modified QBC could be only used where appropriate facilities are available. Advantage mal card was a better follow-up tool than Parahit total.